Desenvolvimento de um cubo de roda para um protótipo Off-Road - Bezerra, William Jhonatan Lopes (Universidade Federal Rural do Semi-Árido, 2019)
The work presents a study about the design methodology used for the design of a wheel hub, this being a suspension component of an off-road vehicle prototype, responsible for allowing the rotation of the wheel, connecting the shaft tip (component without rotation) to the wheel (component with rotation), such component is one of the main to absorb the impacts of the suspension in case of jump and frontal collisions as well as reactions of lateral forces. In this way, the design phases of the search for solutions will be analyzed. The possible solutions were evaluated for their respective technical characteristics such as: resistance, mass, manufacturing. A general assessment is necessary in order to define the best option, where the mandatory and desired requirements for the component under study in a competition vehicle will be taken into account.
Monografia
Keywords: Metodologia de projeto; Baja; Pahl & Beitz; Project methodology; Baja; Pahl & Beitz; ENGENHARIAS::ENGENHARIA MECANICA